Peran Patroli Roda Empat Satuan Sabhara dalam Mencegah Tindak Pidana Pencurian dengan Pemberatan di Polres Purwakarta: The Role of Four Wheel Patrols of the Sabhara Unit in Preventing Criminal Case of Theft under Aggravating Circumstances at the Purwakarta Police Department - Hiskia Yomungga (Police Studies Review, 2021)
Crime of Theft with a Burst is a prominent case in Purwakarta Regency. This was indicated through the basic intelligence of Purwakarta Police Resort in 2019 which showed that the crime amounted to more than one hundred cases from three years back. The police in maintaining Kamtibmas, through preventive measures carried out by the Sabhara function through Patrol activities, are trying to prevent felony. The purpose of this study is to describe and analyze the problems that occur in Purwakarta police in preventing these criminal acts. These problems are analyzed using concepts and theories. The concepts in question include the Role Concept, Patrol Concept, Curat Concept, while the Theories used include Role Theory, Management Function Theory, and Crime Prevention Theory. The author in conducting research based on a qualitative approach with interviews, document studies, and research literature. In carrying out the research the author can find out how the role and stage of the implementation of four-wheeled patrol in Purwakarta Police, and strategies to prevent criminal acts of theft by weighting. Each of the findings then analyzed by the author refers to the concepts and theories. From these results it can be concluded that criminal acts of theft by weighting are still prominent in Purwakarta district. Criminal crimes require the role of a sabhara four-wheeled patrol unit to be increasingly improved in order to be able to prevent a criminal offense. The advice given by the author is that a strict and periodic evaluation is needed to improve the performance of patrol members.